Incidence and risk factor of deep venous thrombosis in patients undergoing craniotomy for brain tumors: A Japanese single-center, retrospective study. Issue 165 (May 2018) - Nakano, Fumi; Matsubara, Toshio; Ishigaki, Tomoki; Hatazaki, Seiji; Mouri, Genshin; Nakatsuka, Yoshinari; Suzuki, Hidenori
Abstract: Introduction: It has been reported that brain tumor resection by craniotomy is a high risk for deep venous thrombosis (DVT), though few data is available in Japanese patients. The aim of this retrospective study was to evaluate the incidence and risk factors for DVT in Japanese adult patients with brain tumor surgery. Materials and methods: Medical records of Japanese adult patients with craniotomy for brain tumor were reviewed. In addition to clinical variables including patients' age, sex, body mass index, previous history of DVT, leg paresis, medications, tumor histology, surgical factors, adjuvant therapy, infection, and duration of post-operative immobilization and hospitalization, plasma D-dimer levels were measured at pre-surgery (baseline), on post-operative day (POD) one to 30 and during adjuvant therapy, and were compared between patients with and without DVT. Results: Thirteen of 61 patients (21.3%) had DVT after surgery with mechanical prophylaxis. All DVTs were asymptomatic. Multivariate analyses found post-operative infection (odds ratio, 12.15; 95% confidence interval, 1.09–134.98; P  = 0.03) to be a sole independent risk factor for DVT. D-dimer levels were not significantly different between patients with and without DVT at baseline and POD 1–30, but were significantly elevated during adjuvant therapy in patients with DVT ( P  = 0.03). Conclusions: Not a few Japanese patients developed DVT after brain tumor surgery with mechanical prophylaxis, and patients with infection should be carefully monitored for post-operative DVT. Highlights: This study first examined post-operative DVT in Japanese brain tumor patients. DVT occurred in 21.3% after brain tumor resection with mechanical prophylaxis. About 77% of DVT cases needed no anticoagulant medication. Infection was an independent risk factor for post-operative DVT. D-dimer levels during adjuvant therapy were significantly increased in DVT cases.